Analisis Kecacatan roti 3 rasa dan roti kering dengan metode Seven Tools di UMKM Bakery Arsyifa - Binang, Arum; Fitria Endrawati, Budiani (LPPM ITK, 2025)
In the industrial world, quality control of a product plays a very important role in increasing competitiveness and consumer interest. Quality control is very necessary to impact the quality of the product produced. If there is no quality control it will have a negative impact on the product, such as defects in the product. In this research, we analyzed 3 types of defects, namely shape defects, color defects and texture defects in 3 flavors of bread and dry bread at UMKM Bakery Arsyifa. The use of implementing methods to reduce defects uses the seven tools method, which consists of several steps, namely check sheet, startification, histogram, scatter diagram, Pareto diagram, control chart, fishbone diagram and improve stage. Based on the results of calculations using the seven tools method, the highest probability results were obtained for 3 flavors of bread, namely texture defects with 119 product defects, dry bread, namely shape defects with 62 product defects. At the fishbone diagram stage, to find out the cause and effect of the defective product, problems were found in man, material, machine, method and carried out the improvement stage using the five m-checklist approach.